A Call to Action: A High Prevalence of Mental Health Conditions in Septic Compared with Aseptic Revision Total Hip Arthroplasty - Warren, Jared; Anis, Hiba K.; Klika, Alison K.; Navale, Suparna; Zhou, Guangjin; Barsoum, Wael; Higuera, Carlos A.; Piuzzi, Nicolas S. (The Journal of Hip Surgery, 2020)
Prosthetic joint infections (PJIs) after primary total hip arthroplasty (pTHA) are known to have a profound impact on patients' pain and function. However, there is little evidence on the association between PJIs and mental health in pTHA and revision total hip arthroplasty (rTHA) patients. The purpose of this study was to compare the prevalence of mental health conditions among patients undergoing (1) pTHA, (2) septic rTHA, and (3) aseptic rTHA. All THAs performed between 2005 and 2014 were queried using the Healthcare Cost and Utilization Project State Inpatient Databases. This yielded 468,663 patients. Patients were separated into the following cohorts based on procedure: primary, septic revision, and aseptic revision. Diagnoses of any mental health condition as well as the following specific conditions were compared among the three cohorts: schizophrenia/delusion, bipolar disorder, depression/mood disorder, personality disorder, anxiety/somatic/dissociative disorder, eating disorders, attention-deficit/hyperactivity disorder/conduct/impulse control, alcohol abuse, and drug abuse. Univariate analysis was performed to assess differences and trends in mental health conditions among the three cohorts. The prevalence of mental health conditions overall in rTHA patients increased throughout the study period. There was a significantly higher prevalence of mental health conditions overall among patients in the septic rTHA cohort (n = 1,818, 28.0%) compared with the pTHA (n = 81,616, 19.2%; p < 0.001), and aseptic rTHA (n = 7,594, 20.9%; p < 0.001) cohorts. Specifically, septic rTHA patients had a higher prevalence of schizophrenia (p < 0.001; p < 0.001), bipolar disorder (p < 0.001; p < 0.001), depression (p < 0.001; p < 0.001), personality disorders (p = 0.0015; p = 0.013), anxiety (p < 0.001; p = 0.0055), eating disorders (p < 0.001; p = 0.006), alcohol abuse (p < 0.001; p < 0.001), and drug abuse (p < 0.001; p < 0.001) compared with primary THA and aseptic rTHA, respectively. Overall, rates of mental health conditions were significantly higher among septic rTHA patients. Alcohol and drug abuse were approximately twice as prevalent among patients undergoing rTHA for infection compared with primary or aseptic rTHA patients. The level of evidence of the study is level III.
Keywords: mental health; THA; PJI; aseptic revision; septic revision